Sam Houston and the Alamo Avengers : The Texas Victory That Changed American History - Kilmeade, Brian (Sentinel, 2019)
"In his now trademark fashion, Brian Kilmeade explores hidden aspects of Sam Houston, the first president of Texas, and brings the reader to the scenes of one of the most pivotal moments in American history. Thanks to Kilmeade's storytelling, a new generation of readers will remember the Alamo"--